IMPLEMENTASI PROGRAM PELITA DALAM MENDUKUNG KEMANDIRIAN EKONOMI MASYARAKAT DI KECAMATAN TANJUNGKERTA KABUPATEN SUMEDANG - Muhamad Firmansyah; Suherman; Lalas Sulastri (JRPA - Journal of Regional Public Administration, 2026)
This research aims to understand the implementation of the PELITA Program in supporting economic self-reliance of the community in TanjungkertaSub-district, Sumedang Regency, as well as to identify the inhibiting factors and the efforts made to overcome those barriers. The research method used is qualitative. The sampling technique employed is purposive sampling, with informants including the Head of Tanjungkerta Sub-district, the Sub-district Secretary, the Head of Human Empowerment Division, and staff members involved in the implementation of the PELITA Program.Data collection techniques include literature review and field studies through observation, interviews, documentation, and triangulation. The data validity techniques applied are credibility, transferability, dependability, and confirmability tests. The data analysis techniques consist of data collection, data reduction, data display, and verification. Based on the research findings, it is concluded that the implementation of the PELITA Program in supporting community economic self-reliance has been effective and has had a tangible impact in reducing extreme poverty—from 28 households in 2023 to 0 households in 2025. However, several obstacles were identified in the program's implementation, such as low community participation, lack of outreach, limited resources, and suboptimal communication between the government and the community. Efforts to overcome these barriers included increasing outreach activities, involving the community in the planning and evaluation process, and strengthening inter-agency coordination. This research include the need for more intensive and sustainable community engagement strategies, increased allocation of resources both human and financial, periodic evaluation of the program’s outcomes, and continuous capacity-building programs for stakeholders involved in PELITA. Furthermore, the government should adopt a more inclusive approach to ensure all community groups are actively involved and benefit from the program.